Autologous hematopoietic progenitor cell mobilization and collection in adult patients presenting with multiple myeloma and lymphoma: A position-statement from the Turkish Society of Apheresis (TSA). Issue 6 (December 2017) - Tekgündüz, Emre; Arat, Mutlu; Göker, Hakan; Özdoğu, Hakan; Kaynar, Leylagül; Çağırgan, Seçkin; Erkurt, Mehmet Ali; Vural, Filiz; Kiki, İlhami and Altuntaş, Fevzi and Demirkan, Fatih and ,
Abstract: Autologous hematopoietic cell transplantation (AHCT) is a routinely used procedure in the treatment of adult patients presenting with multiple myeloma (MM), Hodgkin lymphoma (HL) and various subtypes of non-Hodgkin lymphoma (NHL) in upfront and relapsed/refractory settings. Successful hematopoietic progenitor cell mobilization (HPCM) and collection are the rate limiting first steps for application of AHCT. In 2015, almost 1700 AHCT procedures have been performed for MM, HL and NHL in Turkey. Although there are recently published consensus guidelines addressing critical issues regarding autologous HPCM, there is a tremendous heterogeneity in terms of mobilization strategies of transplant centers across the world. In order to pave the way to a more standardized HPCM approach in Turkey, Turkish Society of Apheresis (TSA) assembled a working group consisting of experts in the field. Here we report the position statement of TSA regarding autologous HPCM mobilization strategies in adult patients presenting with MM and lymphoma.